2001
DOI: 10.1111/1468-5957.00404
|View full text |Cite
|
Sign up to set email alerts
|

The Reversal of the Monday Effect: New Evidence from US Equity Markets

Abstract: This article re-examines the Monday effect in the US stock market from 1964-1999 using daily returns from three large-cap indexes and two small-cap indexes. In the period before 1987, Monday returns are significantly negative in all five US stock indexes, confirming previous empirical findings. In the post-1987 period, we uncover a significant reversal of the Monday effect in the large-cap indexes (NYSE, S&38;P500 and DJCOMP), since Monday returns are significantly positive. Furthermore, significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 8 publications
9
52
0
2
Order By: Relevance
“…In order to determine whether there were any significant differences between the means of stock returns, the one-way analysis of variance (ANOVA) was used. This method was used for re-examines the Monday effect in the U.S. stock market, using daily returns (Mehdian & Perry, 2001) Daily returns of BIST were calculated from the Eq. 1.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine whether there were any significant differences between the means of stock returns, the one-way analysis of variance (ANOVA) was used. This method was used for re-examines the Monday effect in the U.S. stock market, using daily returns (Mehdian & Perry, 2001) Daily returns of BIST were calculated from the Eq. 1.…”
Section: Methodsmentioning
confidence: 99%
“…There are number of studies which have supported the Monday effect in the stock markets (Alt et al, 2011;Cho et al, 2007;Jaffe et al, 1989). However, other studies support the ef icient market hypothesis and are not in line with the Monday effect (Bhana, 1985;Diaconasu et al, 2012;Mehdian and Perry, 2001;Wang et al, 1997). Also, Ajayi et al (2004) Seyyed et al (2005) found the existence of Ramadan effect in Saudi Arabia.…”
Section: Monday Effectmentioning
confidence: 86%
“…This weekend effect is tested all over the world and reported for policy implication and restoring investors' confidence. Monday have significant effect in stock exchange and day of week effect exists in major stock exchange of world as reported [8][9][10][11]. Theories of finance give possible explanation of this weekend anomaly, but researchers thrust is still unfulfilled about it.…”
Section: Literature On Monday Effectmentioning
confidence: 99%